Skip beat! 39 - Nakamura, Yoshiki; Kimura, Tomo (Shojo beat manga., 2017)
Having learned why her mother was so cruel to her as a child, Kyoko steels herself against the ghosts of her past and grows even more determined to become an actress to make the both of them proud.